Incidence and Prevalence of Atherosclerotic Renal Artery Stenosis (RAS) in Patients with Coronary Artery Disease (CAD) (Cardiovascular Journal, 2010)
Background: Aim of our present study was to evaluate the extent of Renal Artery Stenosis(RAS) in patients with Coronary Artery disease (CAD) in context of Bangladesh demographic distribution. Methods: Total 100 patients with renal artery disease were randomized from a pool of 1200 patients who were underwent routine diagnostic coronary angiogram for the evaluation of extent of their CAD. Renal arteries were studied at the same time. Among the patients, Male: 64 and Female: 36. Mean age were for Male: 62yrs, for Female: 58 yrs. Associated CAD risk factors were Dyslipidemia, High Blood pressure, Diabetes Mellitus, Positive FH for CAD and Smoking. Results: Our study results show 100 patients (12% of the sample) had RAS lesion out of total 1200 patient who underwent routine CAG. Sex distribution is male 64 (64%), Female 36 (36%). Among the study group; 79 (79%) were hypertensive; 57 (57%) were Dyslipidemic, 54 (54%) patients were Diabetic, 27 (27%) were smoker (all male) and 18(18%) were having positive FH for CAD. Female patients were more obese and developed CAD in advanced age (male: 53.5 Versus Female:64 yrs). We found that the Prevalence’s of RAS is more in patients with TVD (43%), followed by DVD (10%) and SVD (10%), Minor to mod CAD (14%) and angiographically normal coronaries (23%). Significant (>50% Stenosis) Left renal artery stenosis were found in 27 patient and 23 had significant Right renal artery stenosis. Total 8 patents had significant both renal artery stenosis. Conclusion: Renal artery stenosis is one of the most important peripheral vascular disease, needing to be diagnosed early and subsequent intervention to keep continuity of renal blood flow. In the present study, we found that the significant association of Renal Artery Stenosis in patients with CAD. Incidence of RAS is more in patients with TVD. Therefore, we recommend routine Renal angiogram during coronary angiography. Keywords: Renal artery stenosis; Coronary Artery Disease  DOI: 10.3329/cardio.v2i2.6636Cardiovasc. j. 2010; 2(2) : 179-183